Rice Marketing Value Chain In Makassar Terong Traditional Market - Marina Marina; Didi Rukmana; Letty Fudjaja; A Amrullah; Pipi Diansari (Jurnal Sosial Ekonomi Pertanian, 2020)
This study aims to determine the activities carried out at the level of wholesalers and retailers in Makassar Traditional Eggplant Market and determine the marketing margin of rice in Makassar Traditional Eggplant Market. The number of samples taken as many as 8 retail respondents and as many as 6 respondents of large traders taken by simple random sampling. Analysis of the data used is descriptive analysis to identify rice magnification activities in the Makassar City of Terong Traditional Market and quantitative analysis, which is to analyze marketing margins and rice profit ratios in the Makassar City of Terong Traditional Market with the formula of marketing margin and profit ratio. Activities undertaken by large traders prior to selling are ensuring the amount of rice stock, contacting rice suppliers and making direct and indirect sales while retailers do not conduct a series of activities before selling, at the level of rice traders only conducting sales activities. Marketing margins from retailer which is Rp. 1,705 while the marketing magin at the wholesaler level is Rp. 867.